Sexual communication in day-flying Lepidoptera with special reference to castniids or 'butterfly-moths'. Issue 4 (5th April 2016) - Sarto i Monteys, V.; Quero, C.; Santa-Cruz, M.C.; Rosell, G.; Guerrero, A.
Abstract: Butterflies and moths are subject to different evolutionary pressures that affect several aspects of their behaviour and physiology, particularly sexual communication. Butterflies are day-flying insects (excluding hedylids) whose partner-finding strategy is mainly based on visual cues and female butterflies having apparently lost the typical sex pheromone glands. Moths, in contrast, are mostly night-flyers and use female-released long-range pheromones for partner-finding. However, some moth families are exclusively day-flyers, and therefore subject to evolutionary pressures similar to those endured by butterflies. Among them, the Castniidae, also called 'butterfly-moths' or 'sun-moths', behave like butterflies and, thus, castniid females appear to have also lost their pheromone glands, an unparallel attribute in the world of moths. In this paper, we review the sexual communication strategy in day-flying Lepidoptera, mainly butterflies (superfamily Papilionoidea), Zygaenidae and Castniidae moths, and compare their mating behaviour with that of moth families of nocturnal habits, paying particular attention to the recently discovered butterfly-like partner-finding strategy of castniids and the fascinating facts and debates that led to its discovery.